Factors Influencing the Incidence of Diarrhea in Kepulauan Seribu District, DKI Jakarta - Rudi, Muhammad; Wahyuningsih, Nur Endah; Hanani, Yusniar (Buletin Penelitian Kesehatan, 2024)
Introduction: Diarrhea cases in the Seribu Islands were recorded in 190 cases in 2021 and in 461 cases in 2022. The factors influencing the incidence of diarrhea are knowledge, attitudes and practices, clean water sources, and clean water quality. The aim of the study was to analyze factors related to the incidence of diarrhea in the Seribu Islands District. Methods: This study was conducted in the Seribu Islands District from February to August 2024. This study was an observational analysis with a case-control approach design. The respondent criteria include having a history of diarrhea in the South Seribu Islands District, as showed by a doctor's diagnosis and positive laboratory results for diarrhea from January to December 2022, and having resided there for more than six months. The case group was consisted of 37 samples and the control group consisted of 37 samples. The independent variables in this study were the biological, physical, and chemical quality of clean water, clean water sources, knowledge, attitudes, and practice. The collected data were analyzed using the chi-square and logistic regression test using SPSS software. Results: The variables of physical quality of clean water, clean water sources, knowledge and practices of respondents did not have a significant effect on the incidence of diarrhea (p>0.05). Meanwhile, the biological and chemical quality of clean water, and the respondents' attitudes had a significant effect on the incidence of diarrhea (p <0.05). Based on the results of the multivariate analysis, the biological quality of clean water had a significant effect (p = 0.001) with an odds ratio of 9.18. The most influential factor on the incidence of diarrhea is the biological quality of the clean water. Conclusion: The variables of knowledge, attitudes, practices, clean water sources, and physical and chemical quality of water showed no effect on the incidence of diarrhea (p value > 0.05). The biological quality of the water variable had an effect on the incidence of diarrhea (p value = 0.001), with an odds ratio of 9.18. Since E. coli-contaminated food and water contribute significantly to the spread of diarrheal illnesses in the community, it is crucial to monitor the quality of food and drinking water and to improve sanitation in order to reduce the prevalence of diarrhea, particularly in the Seribu Islands.